2022
DOI: 10.3390/ijerph19095300
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurological Sequelae Successfully Treated with Adjuvant, Prolonged Hyperbaric Oxygen Therapy: Review and Case Report

Abstract: Carbon Monoxide (CO) intoxication is still a leading cause of mortality and morbidity in many countries. Due to the problematic detection in the environment and subtle symptoms, CO intoxication usually goes unrecognized, and both normobaric and hyperbaric oxygen (HBO) treatments are frequently administered with delay. Current knowledge is mainly focused on acute intoxication, while Delayed Neurological Sequelae (DNS) are neglected, especially their treatment. This work details the cases of two patients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…HBO therapy is sometimes performed in patients with DPHL after CO poisoning; some studies have shown its efficacy ( 7 ). However, it remains unclear why HBO is effective in DPHL after CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…HBO therapy is sometimes performed in patients with DPHL after CO poisoning; some studies have shown its efficacy ( 7 ). However, it remains unclear why HBO is effective in DPHL after CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…DNS manifestations include neuropsychiatric symptoms such as cognitive deterioration, sphincters incontinence, a parkinsonismlike condition, akinetic mutism, dystonia, neurological focal symptoms, and depression/anxiety (3)(4)(5). The exact mechanism of DNS development and its incidence are still to be defined (6). A significant problem is represented by a lucid interval between the clinical encounter and DNS development, frequently misleading the recognition and hampering correct treatment.…”
mentioning
confidence: 99%
“…Further studies are needed to determine whether these patients may benefit from a prolonged observation in the emergency department, admission to the ward, and more timely or intense rehabilitative therapy. Also, the best treatment for DNS is still debated, especially regarding the number of HBO 2 treatments, the exact pressures and duration to be used, and whether HBO 2 should be administered alone or with adjuvants such as antioxidant scavengers or corticosteroids (6). Lee et al prospectively analyzed data collected from a registry established in 2006, including 537 patients, and found no differences in the reduction of poor neurocognitive outcomes among patients who received one, two, or three HBO 2 sessions within 24 h after CO poisoning.…”
mentioning
confidence: 99%